EVALUASI AKTIVITAS NON VALUE ADDED DENGAN MENGGUNAKAN METODE VALUE STREAM MAPPING DAN PROCESS ACTIVITY MAPPING - Ilham, Muhammad; Nofirza, Nofirza; Hadiyul Umam, Muhammad Isnaini; Yola, Melfa; Anwardi, Anwardi (Heuristic, 2024)
Samsul Blacksmith is a blacksmith who produces palm harvesting tools (dodos), in the production process there is still waste which causes the daily production target not to be achieved, this study aims to determine the root causes of waste and provide alternative improvements. This research was conducted with 4 stages, first mapping all production activities using value stream mapping (VSM), the second stage identifying waste using the Process activity mapping (PAM) method, the third stage identifying the root causes of waste using the 5 whys method, the last stage providing alternative improvements to reduce or eliminate waste. The results showed that waste occurred due to the absence of workpiece transfer tools and long transfer distances, simple furnaces without the use of heat shields, and inefficient workbenches, the proposed alternative re-layout of the production floor, designing furnaces, and designing work areas, was able to reduce the lead time of the production process from 6.260 seconds to 4.907,8 seconds (improvement with MOST and MTM), and increased the PCE value from 51.6% to 65.8%.